Freezability and fertility of Marwari stallion semen - Pal, Yash; Arangasamy, A; Legha, R A; SINGH, J; BANSAL, R S; KHURANA, S K; TANDON, S N (The Indian Journal of Animal Sciences, 2011)
Variations in freezability of extended raw semen between individual stallions and rate of conception with cryopreserved semen were studied. Semen was collected through artificial vagina (AV) from 14 Marwari stallions (4 collections each) of 4 organized farms. The semen was filtered through a sterilized gauge for removing gel and volume was recorded. Gel free semen was used for evaluation of certain physical and morphological characteristics like initial motility, progressive motility, pH, colour and consistency of semen and total sperm concentration adopting standard methods. Ejaculates with more than 60% progressively motile sperm were further used for freezing using Bio-med planner. Straws were thawed at 37Â°C for 1 min in water bath and evaluated for post-thaw motility. Out of 14 stallions studied, the freezability of semen was observed as good, moderate and poor on the basis of post-thaw motility in 6, 5 and 3 stallions, respectively. A total of 98 estrus mares were monitored with ultrasonography from third day of estrus to the time of ovulation and inseminated near to ovulation using the frozen semen. One, two, three and four AI per cycle were performed in 32, 59, 4 and 3 mares depending upon the expected time of ovulation with conception rate as 31, 47, 75 and 100%, respectively. It is concluded that semen of all the stallions do not freeze alike and for optimum conception rate at least 2 to 3 AI per cycle in mares is preferred.